COVER AND PREFACE JURNAL KONVERSI ENERGI DAN MANUFAKTUR VOL. 8 NO. 1 (2023) - Jurnal Konversi Energi dan Manufaktur Editor's (Jurnal Konversi Energi dan Manufaktur, 2023)
Syaka, et al., in their paper, analyzed the comparisons and differences in variations in setting injection duration and ignition timing for engine power output using Pertamax fuel using experimental methods. Riyadi, et al., in their paper, analyzed the effect of CDI and spark plug variations on the performance and fuel consumption of the Vespa Strada motor. This research was conducted to determine the effect of using variations of the CDI limiter and CDI unlimiter with spark plugs on torque, power, and fuel consumption using Pertamax fuel. Sopiyan, et al., in their paper, conducted experiments with two types of calipers to know the distance and braking time on a 125 cc motorcycle. Riyadi, et al., in their report, conducted experiments with roller weight variations to get the best acceleration value on the Honda Vario 150 automatic motorcycle. Rohmatin, et al., in their paper, discussed the development of chip packaging designs according to customer wishes using the quality function deployment (QFD) method. Muhammad and Yulianto, in their report, determined an excellent overhaul planning using the help of the Python programming language with the linear regression method. Setiawan, et al., in their paper, conducted a simulation analysis and fabrication of the frame to obtain the design of the frame and power for electric motorcycle applications. Juwardi, et al., in their paper, determined the standard time and productivity in the glass cleaning work of building X using the stopwatch time study method.